2013
DOI: 10.1017/jfm.2013.594
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability analysis of a shear layer induced by differential coaxial rotation within a cylindrical enclosure

Abstract: The generation of distinct polygonal configurations via the instability of a Stewartson shear layer is numerically investigated. The shear layer is induced using a rotating cylindrical tank with differentially forced disks located at the top and bottom boundaries. The incompressible Navier–Stokes equations are solved on a two-dimensional semi-meridional plane. Axisymmetric base flows are consistently found to reach a steady state for a wide range of flow conditions, and details of the vertical structure are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 50 publications
(101 reference statements)
1
17
0
Order By: Relevance
“…Nevertheless, the observed agreement confirms that the relation obtained from the potential energy equation for horizontal convection (Winters & Young 2009;Barkan et al 2013) at steady state extends to radial horizontal convection with rotation in cylindrical enclosures. (Stewartson 1957;Hide & Titman 1967;Niino & Misawa 1984;Vo et al 2014Vo et al , 2015. The next section describes the linear stability analysis performed to elucidate the instability mechanisms active in the rotating radial horizontal convection system.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the observed agreement confirms that the relation obtained from the potential energy equation for horizontal convection (Winters & Young 2009;Barkan et al 2013) at steady state extends to radial horizontal convection with rotation in cylindrical enclosures. (Stewartson 1957;Hide & Titman 1967;Niino & Misawa 1984;Vo et al 2014Vo et al , 2015. The next section describes the linear stability analysis performed to elucidate the instability mechanisms active in the rotating radial horizontal convection system.…”
Section: )mentioning
confidence: 99%
“…Geophysical applications provoke interest in baroclinic instability in these flows, though in practice the finite enclosure of this system in laboratory set-ups inevitably render them susceptible to other instability mechanisms, including Stewartson layers arising from differential rotation between interior flow and sidewall shear layers (Stewartson 1957;Hide & Titman 1967;Früh & Read 1999;Vo, Montabone & Sheard 2014, 2015 and thermal instability in regions of strong adverse temperature gradient (Bodenschatz, Pesch & Ahlers 2000;King & Aurnou 2012). A key question for the correct interpretation of laboratory investigations of baroclinically active flows and horizontally driven convection flows with rotation is therefore its global stability to axisymmetric and non-axisymmetric disturbances.…”
mentioning
confidence: 99%
“…This configuration has been studied previously by numerous authors (e.g. Früh & Read 1999;Aguiar 2008;Vo et al 2014Vo et al , 2015 and a schematic of the system is shown in figure 1. The key dimensions adopted here match the physical proportions used by Früh & Read (1999) such that the ratio of the disk and tank radii is R d /R t = 1/2 and the aspect ratio (ratio of the tank height to disk radius) is A = H/R d = 2/3.…”
Section: System Description and Governing Parametersmentioning
confidence: 99%
“…Vo, Montabone & Sheard (2014) were the first to characterize the vertical structure of the axisymmetric base flow and identify azimuthal linear instability modes that can cause polygonal deformations to the Stewartson layer. These shear layers were produced by the differential rotation of disks in a rotating cylindrical tank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation